Tax Revenue and Deficit Budget in Indonesia - Fibria Anggraini Puji Lestari (International Journal of Multidisciplinary Research and Studies, 2023)
The research paper was conducted to clarify the influence between tax revenue and budget deficit in Indonesia. A sample of her 30 provinces in Indonesia was used in this study. The data used were secondary data from 1991 to 2021 and were analyzed using the Eviews 12 application. Based on the results of this study, the rupiah exchange rate and crude oil price variables have a positive and significant influence on tax revenue in both the long and short term, whereas the poverty variable has a negative effect on tax revenue in both the long term and the short term. And tax revenue has a negative influence and is key to the budget deficit.